Fostering open innovations at Make company through educational collaboration - Vinahradava, Anastasiya; Špaček, Miroslav, 1954-; Demir, Ferhat; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This study examines the proposed enhancements to the business model of the Make Academic Alliance, focusing on improving the integration of practical digital skills into academic curricula, fostering sustainable partnerships, and enhancing the overall educational impact. The research draws on comprehensive analysis, including interviews with key stakeholders as VŠE teachers, SWOT analysis, and the current Business Model Canvas. Key recommendations include developing market-specific strategies, expanding and customizing outreach efforts, enhancing integration support for educators, implementing deeper engagement metrics, and fostering industry collaboration. Additionally, the study proposes a VŠE partnership program that enables companies to provide resources for free, creating a win-win scenario for both educators and industry partners. The findings highlight the importance of aligning practical initiatives with academic objectives, leveraging strategic partnerships, and continuously improving through structured feedback mechanisms to ensure the program's scalability and sustainability.
Vedoucí práce: Miroslav Špaček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses